Gas to 2030: Transition, Supply Risk and Market Uncertainty - Bassam Fattouh; Bill Farren-Price (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2024)
This gas-focused edition of the Oxford Energy Forum updates the scorecard on the key issues driving medium to long-term gas demand prospects in key consuming countries. Whether it is European climate policy and the regulation of decarbonized gases, the demand outlook for Asian industrial economies or the political and macroeconomic context for energy transition, this issue attempts to unpick the key themes and challenges in the global gas picture. Beyond the OECD countries, it looks at China, India and Africa from a policy, investment and resource perspective, while also digging into the dynamics of global gas supply that will underpin the growing LNG market.
Keywords: 330